Highly recruited brown adipose tissue does not in itself protect against obesity - Gabriella von Essen; Erik Lindsund; Elaina M. Maldonado; Petr Zouhar; Barbara Cannon; Jan Nedergaard (Elsevier, 2023)
Objective: The possibility to counteract the development of obesity in humans by recruiting brown or brite/beige adipose tissue (and thus UCP1) has attracted much attention. Here we examine if a diet that can activate diet-induced thermogenesis can exploit pre-enhanced amounts of UCP1 to counteract the development of diet-induced obesity. Methods: To investigate the anti-obesity significance of highly augmented amounts of UCP1 for control of body energy reserves, we physiologically increased total UCP1 amounts by recruitment of brown and brite/beige tissues in mice. We then examined the influence of the augmented UCP1 levels on metabolic parameters when the mice were exposed to a high-fat/high-sucrose diet under thermoneutral conditions. Results: The total UCP1 levels achieved were about 50-fold higher in recruited than in non-recruited mice. Contrary to underlying expectations, in the mice with highly recruited UCP1 and exposed to a high-fat/high-sucrose diet the thermogenic capacity of this UCP1 was completely inactivate. The mice even transiently (in an adipostat-like manner) demonstrated a higher metabolic efficiency and fat gain than did non-recruited mice. This was accomplished without altering energy expenditure or food absorption efficiency. The metabolic efficiency here was indistinguishable from that of mice totally devoid of UCP1. Conclusions: Although UCP1 protein may be available, it is not inevitably utilized for diet-induced thermogenesis. Thus, although attempts to recruit UCP1 in humans may become successful as such, it is only if constant activation of the UCP1 is also achieved that amelioration of obesity development could be attained.